Resolution of uremic tumoral calcinosis in a patient on peritoneal dialysis with long-term low-calcium dialysate treatment - Yaerim Kim; Eunah Hwang; Sungbae Park (The Korean Society of Nephrology, 2014)
Tumoral calcinosis is a rare complication in uremic patients. An in-depth review of published literature suggests that most patients with uremic tumoral calcinosis do not respond to medical treatment. Here, we report the case of a patient on peritoneal dialysis who presented with infected multifocal masses on both hip joints and was successfully treated by medical intervention. The patient was diagnosed with uremic tumoral calcinosis by physical examination and radiologic imaging, and treated with low-calcium dialysis and a non-calcium phosphate binder, sevelamer, without increasing the dose of dialysis. At the 36-month follow-up, the majority of masses had disappeared and the patient was asymptomatic.